2003
DOI: 10.1029/2003jd003544
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of free tropospheric aerosol particles at Mt. Tateyama, central Japan

Abstract: Number‐size distribution of atmospheric aerosol particles and O3 concentration were measured at Murododaira (36.6N, 137.6E, 2450 m above sea level (asl)) on the western flank of Mt. Tateyama in central Japan from January 1999 to November 2002. This study used nighttime data from 2400 to 0500 hours (local time) on the basis of analysis of their diurnal variation to characterize free tropospheric aerosols and O3 over Japan. The O3 concentration shows small variability (standard deviation of 4 ppbv) with the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
(44 reference statements)
4
32
0
Order By: Relevance
“…The average daily aerosol concentration is The total carbonaceous mass concentration was also found to be more than two times higher during summer compared to winter at the puy de Dôme (Pio et al, 2007). Seasonal variations of the total particle number concentration have been documented in several environments (Yoon et al, 2007;Rodriguez et al, 2005;Komppula et al, 2000, Nyeki et al, 1998Weingartner et al, 1999;Osada et al, 2003;Van dingenen et al, 2005) with maxima differing according to the site. Compared to the extensive study of Van Dingenen et al (2004) for European sites, the puy de Dôme concentrations fall between those measured at the high altitude site of Jungfraujoch, Switzerland, and those measured at the boundary layer site of Aspvreten in Sweden.…”
Section: Particle Number Concentrationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The average daily aerosol concentration is The total carbonaceous mass concentration was also found to be more than two times higher during summer compared to winter at the puy de Dôme (Pio et al, 2007). Seasonal variations of the total particle number concentration have been documented in several environments (Yoon et al, 2007;Rodriguez et al, 2005;Komppula et al, 2000, Nyeki et al, 1998Weingartner et al, 1999;Osada et al, 2003;Van dingenen et al, 2005) with maxima differing according to the site. Compared to the extensive study of Van Dingenen et al (2004) for European sites, the puy de Dôme concentrations fall between those measured at the high altitude site of Jungfraujoch, Switzerland, and those measured at the boundary layer site of Aspvreten in Sweden.…”
Section: Particle Number Concentrationsmentioning
confidence: 98%
“…Long-term monitoring of aerosol number concentration and size distribution has been performed at several measurement sites in particular in the boundary layer at urban locations (Wehner and Wiedensohler, 2003;Ganguli et al, 2006;lonati et al, 2006;Tuch et al, 2006), at rural and remote sites (Birmili et al, 2001;Mäkelä et al, 2000;Tunved et al, 2003;Rodriguez et al, 2005), in the artic atmosphere , in marine environments (Satheesh et al, 2006;Yoon et al, 2006), and in the free troposphere (Nyeki et al, 1998;Weingartner et al, 1999;Osada et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the dry deposition velocity of sulfate aerosol is much less than that of SO 2 , sulfate aerosols may be transported for longer distances than SO 2 . The transport of SO 2− 4 from the Asian continent to South Korea and Japan has been reported using both back-trajectory analysis (Kitayama et al, 2010;Osada et al, 2003) and the Community Multiscale Air Quality (CMAQ) modeling (Aikawa et al, 2010;. The inter-annual variations of measured SO 2− 4 at EANET sites are shown in Fig.…”
Section: Correlations Between So 2 Emission and So 2 And Somentioning
confidence: 99%
“…Streets et al, 2000Streets et al, , 2006aStreets et al, , 2008Streets et al, , 2009Ohara et al, 2007). Also, the effect of SO 2 emission in the Asian continent on the regional and global environment has been studied by using both chemical transport models (Aikawa et al, 2010;Lin et al, 2008;Osada et al, 2009) and intensive field experiments, e.g., ACE-Asia (Huebert et al, 2003), TRACE-P (Jacob et al, 2003), and INTEX-B (Singh et al, 2009), and most recently by using satellite observations directly (Lee et al, 2008;Li et al, 2010a;van Donkelaar et al, 2008). Taken together, the results of these studies strongly suggested that the generation of sulfur species was increasing over time in this region, and sulfur-containing air pollutants (e.g., sulfate) are transported long distances from the Asian continent to the Northwestern Pacific, North America, and the rest of the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…This model is driven by meteorological fields generated by the Regional Atmospheric Modeling System (RAMS) version 4.4 (Pielke et al, 1992). The horizontal model domain for the CMAQ simulation is 6240×5440 km on a rotated polar stereographic map projection centered at 25 • N, 115 • E, with a grid resolution of 80×80 km.…”
Section: Observation Data Treatment and Numerical Modelmentioning
confidence: 99%